Changes in Impaired Fasting Glucose and Borderline High Low-Density Lipoprotein-Cholesterol Status Alter the Risk of Cardiovascular Disease: A 9-Year Prospective Cohort Study - Wang, Xianxuan; Zhou, Yan-Feng; Huang, Zegui; Yu, Xinran; Chen, Zekai; Cai, Zefeng; Lan, Yulong; Li, Werijian; Cai, Zhiwei; Fang, Wei; Chen, Guanzhi; Wu, Weiqiang; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: We aimed to characterize the relationships of the changes in impaired fasting glucose (IFG) and borderline high low-density lipoprotein-cholesterol (LDL-C) status with cardiovascular disease (CVD). Methods: A total of 36,537 participants who did not have previous CVD, diabetes mellitus, or high LDL-C (≥4.1 mmol/L), nor were taking lipid-lowering drugs were recruited from the Kailuan study (URL: http://apps.who.int/trialsearch/Trial2.aspx?TrialID=ChiCTR-TNRC-11001489; trial registration number: ChiCTR-TNRC-11001489). The participants were allocated to six groups according to their baseline and follow-up fasting blood glucose (FBG) and LDL-C concentrations: 1) both were normal; 2) both normal at baseline, one abnormality subsequently; 3) both normal at baseline, both abnormal subsequently; 4) at least one abnormality that became normal; 5) at least one abnormality at baseline, a single abnormality subsequently; and 6) at least one abnormality, two abnormalities subsequently. The outcomes were CVD and subtypes of CVD (myocardial infarction and stroke). Multiple Cox regression models were used to calculate adjusted hazard ratio (HR) and confidence interval (95% CI). Results: During a median follow-up period of 9.00 years, 1,753 participants experienced a CVD event. After adjustment for covariates, participants with IFG in combination with a borderline high LDL-C status at baseline and follow-up had higher risks of CVD (HR: 1.52; 95% CI: 1.04–2.22 and HR: 1.38, 95% CI: 1.12–1.69, respectively) compared with those with normal fasting blood glucose and LDL-C. Compared with participants that remained normal, those who changed from normality to having two abnormalities were at a higher risk of CVD (HR: 1.26; 95% CI: 0.98–1.61), as were those who changed from at least one abnormality to two abnormalities (HR: 1.48, 95% CI: 1.02–2.15). Conclusions: Changes in IFG and borderline high LDL-C status alter the risk of CVD, implying that it is important to focus on such individuals for the prevention and control of CVD.